2020
DOI: 10.1111/pbr.12864
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of deep‐sowing tolerance during seed germination in the maize IBM Syn4 RIL population

Abstract: In arid or semi‐arid regions, deep‐sowing is an effective treasure to ensure seeds absorbing water from deep soil layer at present. However, the existing maize varieties have poor tolerance to deep‐sowing, which is attributed to that few genes are explored and utilised. In this study, 243 IBM Syn4 recombinant inbred lines (RIL) constructed with B73 and Mo17 as parents and 1,339 DNA markers evenly distributed in 10 chromosomes, were used for QTL analysis of deep‐sowing tolerance during seed germination. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…The unusually poor germination by Mo17 was likely exacerbated by the humid conditions in the growth bags combined with the microbial activity, because germination success was much higher under more realistic field conditions (see Microbe-Dependent Heterosis in Two Field Sites). This aligns with past work demonstrating that the emergence success of Mo17 drops rapidly with excess moisture and other stresses, whereas B73 is less sensitive (12)(13)(14). In the two sterile treatments, B73 and B73xMo17 germinated equally well.…”
Section: Significancesupporting
confidence: 89%
“…The unusually poor germination by Mo17 was likely exacerbated by the humid conditions in the growth bags combined with the microbial activity, because germination success was much higher under more realistic field conditions (see Microbe-Dependent Heterosis in Two Field Sites). This aligns with past work demonstrating that the emergence success of Mo17 drops rapidly with excess moisture and other stresses, whereas B73 is less sensitive (12)(13)(14). In the two sterile treatments, B73 and B73xMo17 germinated equally well.…”
Section: Significancesupporting
confidence: 89%
“…Our previous study also drew a similar conclusion [7]. Several key genes or quantitative trait loci (QTL) related to deep-sowing tolerance were then identified and analyzed in our later research [1,3,8,9]. For instance, Affymetrix GeneChip analysis using a deep-sowing-tolerant maize inbred line, 3681-4, indicated that GA receptor GID1, transcriptional factor MYB, DELLA protein DWRF8 genes might play a critical role in GA3-induced mesocotyl elongation under deep-sowing conditions [4].…”
Section: Introductionmentioning
confidence: 61%
“…In another study, 243 IBM Syn4 recombinant inbred lines (RIL) constructed with B73 and Mo17 as parents were also used for QTL analysis of deep-sowing tolerance, and 7, 7, 5, 10 and 2 QTLs for emergence rate, seedling length, plumule length, mesocotyl length and coleoptile length, respectively, were detected. [9].…”
Section: Introductionmentioning
confidence: 99%
“…The length of seedling, plumule, and mesocotyl were used as indexes of seed germination in abiotic stress [31,32]. In the low-temperature condition, the mesocotyl was too short to measure accurately.…”
Section: Discussionmentioning
confidence: 99%